Development of Rapid Vigor Test Using Urine Sugar Analysis Paper for Soybean (Glycine max L.) Seeds - Rukundo, Jean D’amour; Suhartanto, M. Rahmad; Ilyas, Satriyas (Department of Agronomy and Horticulture, IPB University, 2022)
Seed vigor is an essential parameter of seed quality. It plays a critical value in the decision-making for the seeds to be used in agronomic and horticultural crops. The urinary sugar analysis paper (USAP) test determines seed vigor based on leakage concentration from the seed and corresponding color change of the USAP, which are obtained after soaking the seeds in water. This research was conducted from January 2021 to November 2021, intending to develop a rapid soybean vigor test using USAP, and it was composed of two experiments. Soybean seeds of the Biosoy1 variety were obtained from ICABIOGRAD (Indonesian Center for Agricultural Biotechnology and Genetic Resource Research and Development). The seeds consisted of three different levels of seed lots (low, medium, and high viability with 35%, 64%, and 94% germination percentages, respectively). The first experiment was to determine moisture content and soaking period for the USAP seed vigor test. It was arranged in a completely randomized design with one factor as the combination of three seed lots, two levels of seed moisture content (10-12% and 13-14%), and four levels of the soaking period (0, 6, 8, and 10 hours). The second experiment was the optimization of the soaking period by seed number. It was arranged in a completely randomized design with one factor, which was combinations of three seed lots, three levels of seed numbers (50, 75, and 100 seeds), and the soaking period (four levels as 0, 6, 8, and 10 hours). The data were analyzed statistically by the Minitab package. The result showed that both combinations of 10-12% and 13-14% moisture content with the soaking period of 10 hours effectively differentiated the three seed lots into three vigor levels using USAP. Experiment 2 optimized the soaking period from 10 hours to 8 hours by using 100 seeds. The USAP color change was effectively significant to indicate seed lot vigor levels, mainly based on protein leakage concentration on USAP. The color changes from pale yellow-green for higher vigor seed lot to light greenish-blue for low vigor. The USAP was effective for the soybean vigor test for the seed lot with 10-14% moisture content by soaking 100 seeds into 50 ml of distilled water for 8 hours. The USAP is a promising rapid vigor test method but still needs to be developed further.